The Study of Mangrove Reproductive Phenology in The Rhizophoraceae Family (Bruguiera gymnorrhiza (L.) Lamk., Ceriops tagal (Perr.) C.B. Rob., Rhizophora apiculata Blume. and Rhizophora mucronata Lamk.) - WD. Syarni Tala (Jurnal Biologi Tropis, 2020)
Kendari Bay is directly adjacent to the Kendari City area, so that it receives a lot of pressure mainly from community activities. This pressure causes the declining of mangrove forest area every year. Reproductive phenology of mangroves can be used in planning, collecting seeds, and seeding propagules for rehabilitation of degraded mangrove forest area. The aims of this research were to know the morphological characteristics of mangrove reprodutive organs and mangrove reproductive phenology of Bruguiera gymnorrhiza, Ceriops tagal, Rhizophora apiculata, and Rhizophora mucronata in Kendari Bay. The method using in this research was observation method that conducted directly in the field. Morphology and phenology of mangrove reproduction divided into 6 phases, i.e. flower bud, blooming flower, ovary, fruit, young propagule and mature propagule. The data was analysed descriptively. According to the result, the morphological characteristics of 4 mangrove species were different. Flower of B. gymnorrhiza was single, whereas flowers of C. tagal, R. apiculata and R. mucronata were inflorescences. Ovary of B. gymnorrhiza was hemi inferous, whereas ovaries of C. tagal, R. apiculata and R. mucronata were superous. R. mucronata had the largest propagule compared to other mangroves observed. The timing of mangrove reproductive phenology also showed different result. B. gymnorrhiza required 299 days to develop from flower bud to mature propagule and R. apiculata required 262 days, whereas C. tagal and R. mucronata ÃÂ had not been able known its phenological period because the timing data from ovary to fruit had not been obtained. Further research is needed to resolve this issue.ÃÂ